2003
DOI: 10.1007/s00125-002-1015-2
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oversupply increases Δ9-desaturase expression and its metabolites in rat skeletal muscle

Abstract: Aim/hypothesis. Previous studies have shown that prolonged glucose infusion causes insulin resistance and triglyceride accumulation in rat skeletal muscle. In this study, we investigated a possible relationship between insulin resistance and the composition of different accumulated lipid fractions in rat skeletal muscle. Methods. Continuous glucose infusion was carried out in rats for 7 days. Lipids were extracted from skeletal muscle, separated by thin layer chromatography and fatty acid composition of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…40). The expression of SCD1 but not SCD2 (36) is induced by a high-carbohydrate diet or glucose oversupply in skeletal muscle and in the heart (23,29,36). Glycolytic EDL muscles rely more on glucose supply for their main source of energy and have lower rates of FA oxidation and lower insulin sensitivity than SOL muscles (46,49).…”
Section: Discussionmentioning
confidence: 99%
“…40). The expression of SCD1 but not SCD2 (36) is induced by a high-carbohydrate diet or glucose oversupply in skeletal muscle and in the heart (23,29,36). Glycolytic EDL muscles rely more on glucose supply for their main source of energy and have lower rates of FA oxidation and lower insulin sensitivity than SOL muscles (46,49).…”
Section: Discussionmentioning
confidence: 99%
“…Warensjo et al [23] found that SCD1 activity in serum cholesteryl esters under fasting conditions in humans predicted an increased risk of developing the metabolic syndrome. However, since this association was not independent of obesity and due to the fact that diets with a high amount of saturated fatty acids [36] and glucose [39] increased SCD1 activity, the authors of that report concluded that the observed relationships reflected compensatory upregulation of SCD1 activity to continuous intake of unhealthy diets [23]. Furthermore, in L6 myotubes SCD1 overproduction does not improve insulin signalling in basal conditions, but does protect from fatty acid-induced insulin resistance [40].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the role of particular desaturase enzymes in diabetes and related disorders (6,7,14,21,23). The ⌬ 9 -desaturase enzyme converts saturated fatty acids to monounsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus these enzymes are necessary for the biosynthesis of arachidonic acid, eicosapentaenoic acid, decosahexaenoic acid, and other unsaturated fatty acids (6,7). Insulin therapy reverses and overcorrects the diminished ⌬ 9 -and ⌬ 6 -desaturase activities and restores fatty acid composition to normal, except for the decrease in arachidonic acid (14). Thus alterations in fatty acid composition in tissues from diabetic animals reflect the consequences of insulin deficiency.…”
Section: Discussionmentioning
confidence: 99%